2022
DOI: 10.2478/raon-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Imaging perfusion changes in oncological clinical applications by hyperspectral imaging: a literature review

Abstract: Background Hyperspectral imaging (HSI) is a promising imaging modality that uses visible light to obtain information about blood flow. It has the distinct advantage of being noncontact, nonionizing, and noninvasive without the need for a contrast agent. Among the many applications of HSI in the medical field are the detection of various types of tumors and the evaluation of their blood flow, as well as the healing processes of grafts and wounds. Since tumor perfusion is one of the critical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Our ultimate goal is that the developed FEM model of laser beam-tissue interaction would also prove useful in a clinical setting by aiding the optimal selection of treatment parameters during hair-removal procedures. Using the novel hyperspectral imaging modality [47] could aid in, e.g., collecting information about the quantity of melanin and estimating epidermal thickness, which would in turn be helpful for selecting optimal laser treatment parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Our ultimate goal is that the developed FEM model of laser beam-tissue interaction would also prove useful in a clinical setting by aiding the optimal selection of treatment parameters during hair-removal procedures. Using the novel hyperspectral imaging modality [47] could aid in, e.g., collecting information about the quantity of melanin and estimating epidermal thickness, which would in turn be helpful for selecting optimal laser treatment parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperspectral imaging (HSI) is a sophisticated technology that captures and analyzes fine spectra details at each point in a spatial area [ 23 ]. It can detect unique spectral features of individual objects at different spatial positions which are otherwise visually indistinguishable [ 24 ]. The technical characteristics of HSI include high spectral resolution, continuous, narrow-band image data, and the construction of a three-dimensional (3D) hyperspectral cube containing two-dimensional spatial information (x rows and y columns) and one-dimensional spectral information (wavelength).…”
Section: Introductionmentioning
confidence: 99%
“…The technical characteristics of HSI include high spectral resolution, continuous, narrow-band image data, and the construction of a three-dimensional (3D) hyperspectral cube containing two-dimensional spatial information (x rows and y columns) and one-dimensional spectral information (wavelength). This cube reflects the spectral data generated by the physical structure and biochemical composition differences in the sample, revealing structural and physiological information [ 24 ]. HSI is characterized by its correspondence between spatial and spectral information, non-invasiveness, and high throughput, and it is widely used in agriculture production monitoring, food safety, medical examinations, and other fields [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the technology can be implemented into flexible endoscopes in order to allow a so-called optical biopsy [ 5 ], rigid endoscopes to assist the surgeons during minimal invasive procedures [ 6 ] as well as microscopes to analyze resected tissues [ 7 ]. In several research areas, HSI has shown its great potential to discriminate between several tissue structures by analyzing the tissue–light interactions, measured as specific spectral signatures, allowing tissue perfusion assessment [ 8 , 9 ] and tissue differentiation [ 10 , 11 ]. HSI has been successfully evaluated to detect skin cancer [ 12 , 13 , 14 ], gastric cancer [ 15 ], oral cancer [ 16 ], breast cancer [ 17 ], brain cancer [ 18 , 19 , 20 , 21 , 22 ], head and neck cancer [ 23 ], as well as colorectal cancer [ 24 ] in humans.…”
Section: Introductionmentioning
confidence: 99%